Pemberdayaan Masyarakat Sekitar Hutan Pendidikan Universitas Hasanuddin Desa Rompegading Kabupaten Maros melalui Pengembangan Meliponikultur - Andi Prastiyo; Sitti Nuraeni; Marwan Rajab; Tumanan Tumanan; Isnul Karima Tullah; Nurfadilah Latif; Nirmala Armidha; Marshabilla Marshabilla; Khairunnisa Salsabillah; Andi Mustainah Rusli; Diky Wahyudi (LPPM Universitas Flores, 2022)
The forest bee farmer group in Rompegading Village still has problems regarding the limitions of hunting for forest bees which are only seasonal, safety and environmental risks and limited knowledge of trigona bee cultivation. With the program offered, the community can start a new business, namely trigona bee cultivation independently. The implementation of this program stars from socializing the introduction and potential of trigona bees, opening/cleaning cultivation/meliponiary areas, making bee houses, making paths to bee houses, planting food/flowers around bee houses, making bee boxes, searching for colonies in nature, installation of meliponiary signage, site fencing and monitoring and evaluation of activities. The activity was carried out for approximately 5 months starting from July to November 2021. The first harvest of 500 ml of trigona honey was sold and became a special satisfaction for member of the partner group. The Trigona Bee Thematic Village Development Program as an Effort for Community Empowerment in Rompegading Village, Maros Regency can be considered to have gone well because all activities carried out are carried out according to the scheduled timeline. It is hoped that from this PHP2D, the community of partner forest farmer groups have skills in trigona bee cultivation by utilizing the potential of the surrounding environment, so this can be the first step for them to start a trigona bee cultivation business so that it is hoped that a thematic village that is independent and caring for the environment will be created.